Preintercalation Strategy in Manganese Oxides for Electrochemical Energy Storage: Review and Prospects. Issue 50 (9th November 2020) - Zhao, Qinghe; Song, Aoye; Ding, Shouxiang; Qin, Runzhi; Cui, Yanhui; Li, Shuning; Pan, Feng
Abstract: Manganese oxides (MnO2 ) are promising cathode materials for various kinds of battery applications, including Li‐ion, Na‐ion, Mg‐ion, and Zn‐ion batteries, etc., due to their low‐cost and high‐capacity. However, the practical application of MnO2 cathodes has been restricted by some critical issues including low electronic conductivity, low utilization of discharge depth, sluggish diffusion kinetics, and structural instability upon cycling. Preintercalation of ions/molecules into the crystal structure with/without structural reconstruction provides essential optimizations to alleviate these issues. Here, the intrinsic advantages and mechanisms of the preintercalation strategy in enhancing electronic conductivity, activating more active sites, promoting diffusion kinetics, and stabilizing the structural integrity of MnO2 cathode materials are summarized. The current challenges related to the preintercalation strategy, along with prospects for the future research and development regarding its implementation in the design of high‐performance MnO2 cathodes for the next‐generation batteries are also discussed. Abstract : The intrinsic advantages and mechanisms of the preintercalation strategy in enhancing intrinsic conductivity, activating more active sites, promoting diffusion kinetics, and stabilizing structural integrity of MnO2 cathode materials are reviewed. Simultaneously, the current challenges for the preintercalation strategy for future research and development regarding the design of high‐performance MnO2 cathodes for the next‐generation batteries are discussed.